Effects of invasion games on physical fitness in primary school children - Irena Valantine; Dejan Madić; Goran Sporiš (University of Novi Sad, Faculty of Sport and Physical Education, 2017)
Studies concerning the effects of different invasion games on physical fitness in school children are scarce. Consequently, the purpose of this study was to examine the effects of the application of invasion games on physical fitness in primary school children. A total of 62 primary school children aged 10-12 years voluntarily participated in this study. They were divided into experimental (32) and control (30) group. Physical fitness of children was estimated by the following tests: Standing broad jump, Vertical jump, Bent-arm hang, Sit-ups, Pushups, Medicine ball test and Andersen test. The experimental group had twice per week invasion games on non-consecutive days for 12 weeks. Participants in control group did not perform specific program but attended their regular PE class twice per week. Compared with initial measurement, there was a significant (p < 0.05) improvement in vertical jump test for both groups. Furthermore, the group that participated in the invasion games program made significantly greater gains compared to the control group (p < 0.05) in Standing broad jump (8.2%; ES=0.56 vs. 3%; ES=0.2) and Medicine ball test (8.2%; ES=0.6 vs. 3%; ES=0.3). There was a significant improvement in bent arm hang, sit ups and push-ups in experimental group. Compared with initial measurement, there was a significant (p < 0.05) improvement in Andersen test in invasion games group, which was not the case with control group (p>0.05). To conclude, invasion games were an effective way of improving physical fitness in primary school children, because the results of this study indicate that this method was more effective for physical fitness than traditional school program.